Hybrid Factory: The Japanese Production System in the United StatesHybrid Factory: The Japanese Production System in the United States, edited by AboTetsuo. New York: Oxford University Press, 1994.The Japanese Firm: Sources of Competitive Strength, edited by AokiMasahiko and DoreRonald. New York: Oxford University Press, 1994.Does Ownership Matter: Japanese Multinationals in Europe, edited by MasonMark and EncarnationDennis. New York: Oxford University Press, 1994. - Bird, Allan (Academy of Management Review, 1996)
The article reviews the books, “Hybrid Factory: The Japanese Production System in the United States,” edited by Tetsuo Abo, “The Japanese Firm: Sources of Competitive Strength,” edited by Masahiko Aoki and Ronald Dore, and “Does Ownership Matter: Japanese Multinationals in Europe,” edited by Mark Mason and Dennis Encarnation.